Acute prevertebral abscess as unusual cause of low back pain: Case report - Krstačić Goran J.; Krstačić Antonija J. (Srpsko lekarsko drustvo, 2023)
Introduction: Diseases of prevertebral spaces are uncommon but can result in significant morbidity. Case report: This is a case report of acute prevertebral abscess in a 40year-old man. After being transferred to our hospital the patient was initially diagnosed with lower back pain and with high-grade fever. Magnetic resonance imaging (MRI) suggested prevertebral abscess from Th11-L1. Blood test indicated a bacterial inflammation. Antibiotics were administered. The patient's condition consequently improved. He was discharged with normal neurological status and without any symptoms with a complete regression of the abscess on check-up MRI. Discussion: Magnetic resonance imaging remains the gold standard for the radiological demonstration of spine abscess. Antibiotic therapy is a pillar of treatment for spine abscess and should be a part of the treatment in all cases. Conclusion: In conclusion, our aim is to stress the importance of considering a prevertebral abscess in the differential diagnosis in patient with low back pain.